Forensic drug analysis of chloro-N, N-dimethylcathinone (CDC) and chloroethcathinone (CEC): Identification of 4-CDC and 4-CEC in drug seizures and differentiation from their ring-substituted positional isomers. (May 2019) - Cheng, Wing-Chi; Wong, Wing-Cheong
Graphical abstract: Highlights: GC–CI-MS and LC–DAD developed for analysis of chloro-substituted cathinones isomers. GC–CI-MS identified studied cathinones which showed unique fragmentation patterns. LC–DAD distinguished the para- from its positional isomers with distinct UV spectra. Identifications of chloro-substituted cathinones in drug seizures were demonstrated. Abstract: We report our findings for the determination of 4-chloro-N, N-dimethylcathinone (4-CDC), a newly encountered NPS in drug seizures examined in our laboratory, and its differentiation from 4-chloroethcathinone (4-CEC), one of the most common cathinones examined locally, and their respective regioisomers, namely 2-CDC and 3-CDC, as well as 2-CEC and 3-CEC in routine drug analysis. As CDCs and CECs have the same molecular mass of 211 with similar and non-characteristic spectra when analysed by gas chromatography-electron ionization-mass spectrometer (GC–EI-MS), it is imperative to establish methods easily amendable for forensic laboratories to differentiate these substances unambiguously. To confirm the identity of the solid, reference standards of all regioisomers of CDC (i.e., 2-CDC, 3-CDC and 4-CDC) and CEC (i.e., 2-CEC, 3-CEC and 4-CEC) were acquired and analysed using GC–EI-MS, liquid chromatography-diode array detector (LC–DAD) and Fourier Transform Infrared Spectrophotometer (FTIR) commonly used in routine forensic drug analysis. In addition, drug analysis with gas chromatography-chemical ionization-mass spectrometer (GC–CI-MS) using methane as the reagent gas operated in positive mode was also explored. It is found that using GC–EI-MS, all isomers of CDCs and CECs eluted with close but different retention times. However, the mass spectra between respective regioisomers were similar and difficult to distinguish. Using LC–DAD, the retention times of all studied cathinones were again different although there were partial overlap between 3-CDC and 4-CDC as well as between 3-CEC and 4-CEC but they all have distinguishable UV spectra. Apart from the detection of quasimolecular ion as the most prominent ion for each cathinone, GC–CI-MS is considered a superior technique to determine all six cathinones where each cathinone showed a unique fragmentation pattern for ease of identification. The analytical techniques have been applied for the examination of drug seizures where 4-CDC and 4-CEC were unambiguously identified either as a single component or mixed components in the seized materials. While FTIR is capable of providing confirmative structural information for the cathinones with each regioisomer exhibits a distinctive pattern but requiring high drug purity, LC–DAD and GC–CI-MS are demonstrated to be useful techniques that can readily differentiate structurally similar synthetic cathinones (even in mixtures) for routine forensic drug analysis.